2020
DOI: 10.1177/0300060520904814
|View full text |Cite
|
Sign up to set email alerts
|

Association between thyroid hormone parameters during early pregnancy and gestational hypertension: a prospective cohort study

Abstract: Objective: Thyroid dysfunction may play a role in the development of gestational hypertension. However, this relationship remains unclear. This study was performed to evaluate the association between thyroid hormone parameters during early pregnancy and gestational hypertension. Methods: Women with singleton pregnancies were recruited into this prospective cohort study at 9 to 13 gestational weeks, and their serum thyroid-stimulating hormone, free thyroxine, and free triiodothyronine concentrations were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…In addition, our study did not find that SCH increased the incidence of pregnancy-induced hypertension, while Wilson et al 24 and Lai et al 34 showed that the incidence of pregnancy-induced hypertension in SCH was significantly increased. Consistent with our findings, Casey et al 35 found that there was no significant difference in the prevalence of either the incidence of high blood pressure during pregnancy or severe preeclampsia in the first trimester between SCH women and euthyroid women.…”
Section: Discussioncontrasting
confidence: 81%
“…In addition, our study did not find that SCH increased the incidence of pregnancy-induced hypertension, while Wilson et al 24 and Lai et al 34 showed that the incidence of pregnancy-induced hypertension in SCH was significantly increased. Consistent with our findings, Casey et al 35 found that there was no significant difference in the prevalence of either the incidence of high blood pressure during pregnancy or severe preeclampsia in the first trimester between SCH women and euthyroid women.…”
Section: Discussioncontrasting
confidence: 81%
“…We then further searched the full texts of 40 articles to assess their eligibility, of which 15 were case-control studies, 2 studies were poorly defined for disease, and 2 studies that did not provide HDP-related data were excluded. Eventually, we included 22 original studies to investigate the relationship between subclinical hypothyroidism in pregnancy and HDP (7,10,11,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). (10)].…”
Section: Search Resultsmentioning
confidence: 99%
“…However, some relevant studies have been published recently, proposing some new conclusions. The results of two recently completed prospective cohort studies indicate that subclinical hypothyroidism in pregnancy is associated with an increased risk of developing HDP and is a risk factor for HDP ( 26 31 ). Similarly, the study by Cakmak and Wu, M.Q reached the same conclusion ( 4 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Se deprivation may impair correct function of antioxidant Se-dependent enzymes -glutathione peroxidases and thioredoxin reductases -compromising antioxidant defence pathways, which could lead to endothelial dysfunction observed in the pathophysiology of HDPs (49; 51) . Additionally, Se deficiency could contribute to HDPs by disturbing thyroid function and increasing TSH production (52) which has been suggested as a risk factor for gestational hypertension (53) . Three studies of this review (24; 26; 38) measured Se levels in the first trimester of pregnancy, i.e., before the diagnosis of HDPs (after 20 weeks) took place, and two of them (26; 38) ("good" studies) found a negative association between Se and HDPs.…”
Section: Discussionmentioning
confidence: 99%